MODEL VIDEO PEMBELAJARAN BERBASIS ANIMASI SEBAGAI SOLUSI BELAJAR EFEKTIF DI MASA PANDEMI COVID-19 - Muhibah, Siti (Universitas Sultan Ageng Tirtayasa, 2021)
Thepurposeofthisserviceistoprovidealternativesolutionsforstudentsforeffectivelearning byusinganimation-basedvideolearningmediaasaneffectivelearningsolutionduringthe Covid-19 pandemic. Thelocation ofthe serviceislocated at SD Negeri Karundang1, Karundang Village, Cipocok JayaDistrict, SerangCity. Theform of this serviceactivityis partnership-based withtheschoolandthedistributionoflearning videosonceaweekandtheuseofquestionnaires. The mainmethodusedinthe service isthecreationof animation-basedlearningvideosthrough doratoonwiththeongoingcurriculumadjustmentsatSDNegeri1Karundang.The targetof this service is5thgradestudentsatSDNegeriKarundang1,KarundangVillage,CipocokJaya District,SerangCity.Theoutputtargetandimpacttobeachievedby thisserviceistoincrease studentachievementby utilizinganimation-basedlearning videosthatonlinelearning becomes effectiveduringthe Covid-19 pandemic